Air quality status during 2020 Malaysia Movement Control Order (MCO) due to 2019 novel coronavirus (2019-nCoV) pandemic - Abdullah S.; Mansor A.A.; Napi N.N.L.M.; Mansor W.N.W.; Ahmed A.N.; Ismail M.; Ramly Z.T.A. (Elsevier B.V., 2023)
Air quality; Road vehicles; Air quality monitoring stations; Fine particulate matter (PM2.5); Hazardous air pollutants; Movement control; PM2.5 concentration; Quality status; Reducing emissions; Respiratory illness; Quality control; air quality; atmospheric pollution; concentration (composition); COVID-19; disease control; disease incidence; epidemic; infectious disease; particulate matter; pollution monitoring; respiratory disease; viral disease; air pollutant; Air Pollutant Index; air quality; Article; communicable disease control; coronavirus disease 2019; environmental factor; environmental parameters; epidemic; Malaysia; movement control order; pandemic; particulate matter; priority journal; Severe acute respiratory syndrome coronavirus 2; air pollution; Betacoronavirus; China; Coronavirus infection; human; virus pneumonia; Malaysia; Coronavirus; Air Pollution; Betacoronavirus; China; Coronavirus Infections; Humans; Malaysia; Pandemics; Pneumonia, Viral